Dissecting Aneurysm in Cervical Artery Dissection: Insights From the STOP-CAD Study - Khan, Muhib; Keser, Zafer; Shu, Liqi; Lee, Elizabeth; Ho, Melanie; Klein, Piers; Nguyen, Thanh N. (Lippincott Williams & Wilkins, 2026)
BACKGROUND:Cervical artery dissection (CeAD) may result in dissecting aneurysm (DA) formation. We aimed to characterize risk factors and clinical outcomes associated with DA in a large, international CeAD cohort.METHODS:We performed a secondary analysis of STOP-CAD (Antithrombotic Treatment for Stroke Prevention in Cervical Artery Dissection), an international, multicenter, retrospective cohort. Patients with spontaneous CeAD were assessed for DA at baseline and de novo DA formation. Significant covariates in univariable analysis were included in multivariable regression models aiming to identify factors associated with DA formation. Logistic regression and Cox proportional hazards models evaluated the association of DA with ischemic and hemorrhagic outcomes.RESULTS:Among 4008 patients with CeAD, 546 (13.6%) had a DA at baseline, and 221/2938 (7.5%) patients developed a de novo DA during follow-up, of which 172/221 (78.2%) were detected in the first 180 days. Patients with DA had a mean age of 47 years, and 383 (49.9%) were women. Baseline or de novo DA was associated with a history of connective tissue disorder (adjusted odds ratio [aOR], 2.02 [95% CI, 1.22-3.36]), fibromuscular dysplasia (aOR, 1.69 [95% CI, 1.28-2.25]), and multiple vessel dissection (aOR, 1.53 [95% CI, 1.19-1.98]). Lower odds of DA were seen in Hispanic ethnicity (aOR, 0.64 [95% CI, 0.43-0.97]) and ischemic stroke presentation (aOR, 0.41 [95% CI, 0.34-0.49]). Fibromuscular dysplasia was associated with de novo DA formation (aOR, 2.30 [95% CI, 1.52-3.49]). DA was not associated with ischemic stroke (hazard ratio, 0.71 [95% CI, 0.44-1.16]; P=0.173) or intracranial hemorrhage (HR, 1.09 [95% CI, 0.42-2.84]; P=0.86) by day 180.CONCLUSIONS:DAs are relatively common manifestations of CeAD, typically occurring within 6 months of CeAD diagnosis. DA was not associated with an increased risk of subsequent ischemic stroke or intracranial hemorrhage.
Keywords: aneurysm; arteries; ischemic stroke; risk factor